The merit of corn biological products used in-furrow - Clark, Allicia (Kansas State University, 2021)
Increased corn production to feed and fuel over 7 billion people worldwide over the past few decades has been accomplished by advances in technology and management practices. This thesis focuses on corn fertility management practices, specifically nitrogen management and how the use of corn biological products used in-furrow at planting can be a sustainable practice for the industry while providing net profit gains for the farmer. Nitrogen is a macronutrient required by corn to produce yields. Providing the right amount of nitrogen is essential in maximizing the plants potential genetic yield. Synthetic nitrogen fertilizer, such as anhydrous ammonia, has been industrialized over the past decade and provides for an affordable nitrogen source for farmers to incorporate into their fertility management practices. These synthetic nitrogen fertilizers have been over-applied to the earth’s soils over the last decade as farmers try to push corn yields. As synthetic nitrogen fertilizers are applied in abundance, nitrogen loss is becoming a growing concern for sustainability. The limiting factors of nitrogen fertilizers are surface run-off and soil erosion, rainwater leaching, gaseous losses by volatilization, and microbial consumption. These factors lead to increased levels of nitrogen fertilizers being applied to counteract fluctuating levels of nitrogen from impacting corn yields. This practice is beginning to have negative impacts on ecosystems and waterways, it has increased dead zones, and reduced air quality. Biological products have been introduced as an attempt to combat the negative impacts from synthetic Nitrogen fertilizers. Biological products contain living organisms that, when incorporated into soils, increase soil fertility and productivity. These products also fixate nitrogen naturally through the roots of the corn plant. There are many potential benefits to using these products such as reducing nitrogen costs for the farmer while maintaining or increasing corn yields. This thesis evaluates trials using biological products to determine their merit in providing such benefits to the farmer. This thesis analyzes 60 trials from three sources to determine the merit of corn biological products applied in-furrow. The results indicate that there is a statistically significant average yield advantage of 7.5 bushels per acre from using biological products in-furrow at planting. Using corn prices and biological product costs, a positive return on investment (ROI) is also demonstrated. Thus, incorporating biological products into fertility management programs can reduce nitrogen costs for the farmer while having the potential to gain yields and increase net profits based on the data provided in this thesis. Although the data presented in this thesis aids in the merit of corn biological products used in-furrow at planting, additional research trials should be conducted by agricultural retail companies such as Growmark. Following fertilizer labels, conducting and understanding soil tests, and practicing sustainability methods such as the 4R Stewardship is recommended.
Keywords: Macronutrient; Corn production; Biologicals; Field trial; Agribusiness